Literature Review: Asuhan Gizi Pada Penderita Diabetes Mellitus (DM) di Layanan Primer - Rachmat Faisal Syamsu; Amirah Mardhiyah; Sri Sulfianti (Pelantar Press, 2025)
Diabetes Mellitus (DM) is a major global and national health concern with a steadily increasing prevalence, particularly in Indonesia and South Sulawesi. The primary contributing factors include shifts toward modern lifestyles, obesity, and unhealthy dietary patterns. This literature review employs a library research method with descriptive analysis of various relevant sources, including previous studies and clinical guidelines related to nutritional management of DM. The findings indicate that the implementation of a systematic and standardized nutrition care process significantly improves patient adherence to dietary interventions and glycemic control. Dietary interventions tailored to individual conditions, supported by education and telemedicine technology, play a critical role in enhancing health outcomes and reducing DM-related complications. The effective application of a standardized nutrition care process can improve the quality of DM management in primary healthcare centers, positively contribute to better nutritional status and glycemic control among patients, and support the sustainability and success of DM control programs